The Effect of the Cash Ratio on the Operating Profit Case Study at PT. Pupuk Indonesia year 2019-2023 - Ulawati Fauziah, Nurul; Noor, Sa'ad (International Research & Development for Human Beings (IRDH), 2024)
This study clarified the relationship between profitability and liquidity by concentrating on how the cash ratio affects operating profit. The purpose of this study, which uses Pearson's correlation analysis technique and R-Square analysis technique, is to determine and investigate the impact of the cash ratio on the company's operating profit in greater detail. It is hoped that this study will further shed light on the relationship between liquidity management and the operational performance of companies. The research relies on PT Pupuk Indonesia's annual financial data from 2019 to 2023 is used as the basis for the research. Operating profit is a dependent variable, and cash ratio is an independent variable. The analysis's findings indicate a strong relationship between operating profit and PT Pupuk Indonesia's cash ratio. According to the results of the R Squrared determination test, the cash ratio can explain as much as 81.7% of the variation in operating profit. In this study, PT Pupuk Indonesia's cash ratio and operating profit were found to be significantly positively correlated. These results show that the improvement in the company's operating performance can be attributed to increased liquidity. Nevertheless, the management of PT Pupuk Indonesia must take into account other elements that can impact the company's profitability, such as market conditions, marketing tactics, and cost effectiveness, to create a better long-term strategic plan.